Prognostic significance of CT-emphysema score in patients with advanced squamous cell lung cancer - Kim, Young Saing; Kim, Eun Young; Ahn, Hee Kyung; Cho, Eun Kyung; Jeong, Yu Mi; Kim, Jeong Ho (Journal of Thoracic Disease, 2016)
Background: Although emphysema is a known independent risk factor of lung cancer, no study has addressed the prognostic impact of computed tomography (CT)-emphysema score in advanced stage lung cancer. Methods: For 84 consecutive patients with stage IIIB and IV squamous cell lung cancer that underwent palliative chemotherapy, severity of emphysema was semi-quantitatively scored using baseline chest CT images according to the Goddard scoring system (possible scores range, 0–24). The cutoff of high CT-emphysema score was determined using the maximum chi-squared test and the prognostic significance of the high CT-emphysema score was evaluated using Kaplan-Meier analysis and Cox proportional hazards analysis. Results: The median CT-emphysema score was 5(range, 0–22). Patients with a high CT-emphysema score (≥4) tended to have poorer overall survival (OS) (median: 6.3 vs. 13.7 months) than those with a score of